2023
DOI: 10.1093/plcell/koad117
|View full text |Cite
|
Sign up to set email alerts
|

Phytochromes enhance SOS2-mediated PIF1 and PIF3 phosphorylation and degradation to promote Arabidopsis salt tolerance

Abstract: Soil salinity is one of the most detrimental abiotic stresses affecting plant survival, and light is a core environmental signal regulating plant growth and responses to abiotic stress. However, how light modulates the plant’s response to salt stress remains largely obscure. Here, we show that Arabidopsis (Arabidopsis thaliana) seedlings are more tolerant to salt stress in the light than in the dark, and that the photoreceptors phytochrome A (phyA) and phyB are involved in this tolerance mechanism. We further … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 107 publications
1
23
0
Order By: Relevance
“…It was previously shown that heterologous overexpression of a hyperactive mutant of oat phyA (serine 599 mutated to alanine) in turfgrass enhances its tolerance to high salinity and heavy metal toxicity by increasing chlorophyll content, total biomass, and photosynthetic efficiency (Gururani et al., 2016). Consistent with these observations, a recent study reported that Arabidopsis phyA‐211 , phyB‐9 , and phyA‐211 phyB‐9 mutants all displayed salt‐sensitive phenotypes in the light, indicating that both phyA and phyB positively regulate salt tolerance (Ma et al., 2023) (Figure 3). A previous study showed that Arabidopsis seedlings overexpressing PIF4 exhibited a salt‐sensitive phenotype, indicating that PIF4 acts as a negative regulator of salt tolerance (Sakuraba et al., 2017).…”
Section: Plant Response Strategies To Both Shade and Abiotic Stresssupporting
confidence: 72%
See 3 more Smart Citations
“…It was previously shown that heterologous overexpression of a hyperactive mutant of oat phyA (serine 599 mutated to alanine) in turfgrass enhances its tolerance to high salinity and heavy metal toxicity by increasing chlorophyll content, total biomass, and photosynthetic efficiency (Gururani et al., 2016). Consistent with these observations, a recent study reported that Arabidopsis phyA‐211 , phyB‐9 , and phyA‐211 phyB‐9 mutants all displayed salt‐sensitive phenotypes in the light, indicating that both phyA and phyB positively regulate salt tolerance (Ma et al., 2023) (Figure 3). A previous study showed that Arabidopsis seedlings overexpressing PIF4 exhibited a salt‐sensitive phenotype, indicating that PIF4 acts as a negative regulator of salt tolerance (Sakuraba et al., 2017).…”
Section: Plant Response Strategies To Both Shade and Abiotic Stresssupporting
confidence: 72%
“…A previous study showed that Arabidopsis seedlings overexpressing PIF4 exhibited a salt‐sensitive phenotype, indicating that PIF4 acts as a negative regulator of salt tolerance (Sakuraba et al., 2017). Consistently, pifq mutant seedlings displayed increased resistance to NaCl treatment in the dark, indicating that PIFs negatively regulate salt stress tolerance (Ma et al., 2023) (Figure 3). Salt‐activated SOS2 directly phosphorylates PIF1/PIF3 to decrease their stability and relieve their repressive effect on plant salt tolerance (Ma et al., 2023).…”
Section: Plant Response Strategies To Both Shade and Abiotic Stressmentioning
confidence: 53%
See 2 more Smart Citations
“…This idea is supported by the observations on PAPP2C and PAPP5 phosphatases that are active in the nucleus (Ryu et al ., 2005; Phee et al ., 2008; Fig. 2) and that phyB interacts with a kinase in the nucleus that phosphorylates PIFs resulting in modified light signaling (Ma et al ., 2023). Thus on the one hand, nuclear phyB phosphorylation is an important subject to study and, specifically, phosphorylation of nuclear phyB is expected to be detected.…”
Section: General Conclusion Remaining Questions and Perspectivesmentioning
confidence: 99%